2019
DOI: 10.37190/epe190111
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of influence of coagulation/flocculation and Fenton oxidation with iron on landfill leachate treatment

Abstract: Landfill leachates (LFL) collected from Sfax (Tunisia) discharge area are characterized by high chemical oxygen demand (COD), ammonium and salts contents. They constitute a source of phytotoxicity and pollution for ground water and surface water resources which requires an adequate treatment process. To evaluate the efficiency of the coagulation/flocculation treatment, special attention was paid to the effect of pH, coagulant and flocculant doses. Then, effect of zero valent iron was also studied alone and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The operation of a landfill and the physical, chemical and biological transformations occurring within it result in the emergence of numerous environmental hazards due to, inter alia, emissions of landfill gases, microorganisms or leachates [1]. Leachate is infiltration waters flowing through the landfill cap along with both the waste components washed out and dissolved in them and the products of biochemical reactions occurring in the waste bed [2][3][4][5]. The resulting highly concentrated leachate waters require specialized treatment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The operation of a landfill and the physical, chemical and biological transformations occurring within it result in the emergence of numerous environmental hazards due to, inter alia, emissions of landfill gases, microorganisms or leachates [1]. Leachate is infiltration waters flowing through the landfill cap along with both the waste components washed out and dissolved in them and the products of biochemical reactions occurring in the waste bed [2][3][4][5]. The resulting highly concentrated leachate waters require specialized treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, advanced oxidation processes (AOP) such as photo-Fenton (UV/H 2 O 2 +Fe 2+ ), electro-Fenton, ozone (O 3 ) oxidation, oxidation O 3 +UV, O 3 +UV+H 2 O 2 , percarbonate oxidation or the Fenton process (H 2 O 2 +Fe 2+ ) are increasingly applied. In view of, inter alia, the wide range of application, the high non-selectivity of the • OH, and the simplicity of running the process, the Fenton process is the most popular of the AOP methods, and its main disadvantage is the generation of sediments which need to be properly managed [2,5,6,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, different physicochemical treatments have been tested in leachate, including membrane filtration (Costa et al, 2019), coagulationflocculation, flotation, adsorption, Fenton oxidation (Méndez et al, 2009;Aftab and Hur, 2019;Smaoui et al, 2019, Zhang et al, 2019, Fenton/coagulation (Wu et al, 2010;Luo et al, 2019), heterogeneous Fenton and electrofenton (Sruthi et al, 2018), electrocoagulation with fiber filtration (Li et al, 2017), electrofenton with different doses of H 2 O 2 and Fe 2+ (Mohajeri et al, 2019) and using of sodium sulphate with H 2 O 2 in an advanced oxidation process (Hilles et al, 2016), among others. However, there is no treatment or treatment set have been found that achieve satisfactory removal in leachates and residue generated that being disposed under the applied normativity and are also economically feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Different sources of UV radiation have already been assessed in their application to perform the photo-Fenton reaction, namely, high-pressure mercury-vapor immersion lamps [7,21], sunlight concentrated in compound parabolic collectors (CPC) [23,24], unconcentrated sunlight in thin film reactors [25], and light-emitting diodes (LEDs) [26]. In particular, Singa et al (2018) [21] addressed a 68% COD removal in 90 min of treatment using a 16 W high-pressure mercury-vapor immersion lamp to perform the photo-Fenton degradation of LL.…”
Section: Introductionmentioning
confidence: 99%